Biostratigraphic Evidence Relating to the Age‐Old Question of Hannibal's Invasion of Italy, II: Chemical Biomarkers and Microbial Signatures. (16th March 2016) - Mahaney, W. C.; Allen, C. C. R.; Pentlavalli, P.; Kulakova, A.; Young, J. M.; Dirszowsky, R. W.; West, A.; Kelleher, B.; Jordan, S.; Pulleyblank, C.; O'Reilly, S.; Murphy, B. T.; et al.
Abstract : As discussed in Part I, a large accumulation of mammalian faeces at the mire site in the upper Guil Valley near Mt. Viso, dated to 2168 cal 14 C yr., provides the first evidence of the passage of substantial but indeterminate numbers of mammals within the time frame of the Punic invasion of Italia. Specialized organic biomarkers bound up in a highly convoluted and bioturbated bed constitute an unusual anomaly in a histosol comprised of fibric and hemist horizons that are usually expected to display horizontal bedding. The presence of deoxycholic acid and ethylcoprostanol derived from faecal matter, coupled with high relative numbers of Clostridia 16S rRNA genes, suggests a substantial accumulation of mammalian faeces at the site over 2000 years ago. The results reported here constitute the first chemical and biological evidence of the passage of large numbers of mammals, possibly indicating the route of the Hannibalic army at this time. Combined with the geological analysis reported in Part I, these data provide a background supporting the need for further historical archaeological exploration in this area.